Frequency And Predictors of Acute Kidney Injury in Patients With Decompensated Liver Cirrhosis - nisa, Amar-un-; Ali, Asif; Khan, Ali Khizar; Malik, Shahzeena; Yaqoob, Rabia (Biological and Clinical Sciences Research Journal, 2025)
Acute kidney injury (AKI) is a common and life-threatening complication in patients with decompensated liver cirrhosis, leading to increased morbidity and mortality. Identifying risk factors for AKI in cirrhotic patients is crucial for early intervention and better clinical outcomes. However, limited data exist regarding the prevalence and predictors of AKI in decompensated cirrhotic patients in Pakistan. Objective: This study aimed to determine the prevalence, risk factors, and clinical impact of AKI in patients with decompensated liver cirrhosis admitted to a tertiary care hospital in Pakistan. Methods: A cross-sectional study was conducted at the Department of Medicine, Ibn-e-Sina Hospital, Multan, over six months (April 2024 to November 2024). A total of 121 patients with decompensated liver cirrhosis were enrolled using non-probability consecutive sampling. AKI was diagnosed based on Kidney Disease Improving Global Outcomes (KDIGO) criteria. Data on demographics, comorbidities, medication use, and laboratory parameters were collected and analyzed using SPSS version 25. Statistical tests, including the chi-square test and logistic regression, were used to determine the association between risk factors and acute kidney injury (AKI). A p-value < 0.05 was considered statistically significant. Results: The incidence of AKI was 34.7% (42/121). The mean Child-Pugh-Turcotte (CPT) score was significantly higher in AKI patients (11.6 ± 2.1) compared to non-AKI patients (9.8 ± 2.0, p<0.001). Diabetes mellitus (60% vs. 30%, p=0.002) and nephrotoxic drug use (43% vs. 21%, p=0.01) were significant predictors of AKI. Logistic regression analysis showed that diabetes (OR=2.8, 95% CI: 1.4-5.6, p=0.002), nephrotoxic drug use (OR=2.5, 95% CI: 1.2-5.2, p=0.01), and CPT score ≥10 (OR=3.9, 95% CI: 1.9-8.0, p<0.001) were independent predictors of AKI. Conclusion: AKI is prevalent in patients with decompensated liver cirrhosis, with higher CPT scores, diabetes mellitus, and nephrotoxic drug use identified as key risk factors. Early identification and implementation of preventive strategies are crucial for improving renal outcomes in patients with cirrhosis. Further prospective studies are recommended to validate these findings and develop evidence-based management guidelines.